Improving Narrative Paragraph Writing Abilities Through Inquiry Method: A Classroom Action Research Study - Btr, Ali Amran; Kartolo, Rahmad; Sutikno; Hasibuan, Ahmad Laut; Jalaluddin, Muhammad (International Journal of Educational Research Excellence, 2026)
This study aims to obtain data on improving the ability to write narrative paragraphs using the inquiry method of class X students of SMK Negeri 1 Siabu. By implementing this study, it is hoped that it will be known whether by applying the inquiry method in Indonesian language learning, students' writing abilities can be improved. This study uses a classroom action research method with the aim of improving and enhancing the quality of learning. Data collection tools were taken through tests aimed at class X students of SMK Negeri 1 Siabu in the 2025-2026 academic year. The sample for this study was aimed at classes X-2 and X-4 with a total of 49 students consisting of two classes. Based on the results of classroom action research that has been carried out in two cycles with the use of legend stories in Indonesian language learning for class X students of SMK Negeri 1 Siabu in the 2025-2026 academic year, it can be concluded that there is an increase in the ability to write narrative paragraphs in class X students of SMK Negeri 1 Siabu in the 2025-2026 academic year. After implementing learning with the inquiry method in Indonesian language learning. This can be seen from the average value of students' ability to write narrative paragraphs which continues to increase in cycle I, the average value of students' writing ability is 62.59 with student learning completeness of 28.57% while in cycle II the average value of students' ability increases to 86.42 with learning completeness of 95.91%, when compared to the KKM whichset at 75 with learning completion of 80%.